(untitled) (Global Psychiatry Archives, 2026)
As the world faces multiple crises—wars and conflicts, climate change, and increasing social and political polarization—psychiatry as a discipline stands at a critical juncture. At the same time, the forthcoming revision of DSM-5-TR, in which the “S” shifts from Statistical to Scientific, reflects broader tensions within the field. Psychiatry is increasingly challenged by the anti-psychiatry movement, by new lines of investigation and intervention, and by societal debates around neurodivergence and the over-psychiatrization of normal human responses. Meanwhile, climate change, mass displacement within and across borders, protracted conflicts, economic precarity, and political instability are no longer background stressors. They are at the forefront of everyday pressures, reshaping emotional life, social bonds, and expectations about the future. In this context, psychiatry must confront an uncomfortable question: what does relevance mean when distress is structurally produced rather than individually generated? Importantly, many of these forces now move rapidly across national borders, amplifying their reach and impact.